Implementasi Kebijakan Work Form Home (WFH) di Dinas Komunikasi dan Informatika Kabupaten Banyumas - Oti Kusumaningsih; Ranjani Ranjani; Sartono Sartono; Aditya Garik Waskita Nugraha (Universitas Sultan Ageng Tirtayasa, 2022)
The Covid-19 pandemic urges the government to take preventive steps from the transmission of Covid-19. One of the policies adopted by the government is the change in the work system to work from home or Work From Home (WFH). This study aims to analyze how the implementation of work from home (WFH) policies in the Communication and Information Office of Banyumas Regency. The method used in this research is a qualitative method in the form of a fixed case study. The results of this study indicate that the implementation of the Work From Home Policy at the Communication and Information Office of Banyumas Regency has been able to fulfill the spatial aspect well, namely in the form of transforming the personal space of the employee's house at the Banyumas Regency Communication and Information Office by maximizing various existing devices and technologies that are considered comfortable to work with. In terms of time, employees of the Banyumas Regency Communication and Information Office are able to adapt to two different time situations, namely cyclic time and linear time. This shows that the harmonization of official and family support is able to fulfill the time aspect well. Meanwhile, in the aspect of social roles, the Banyumas Regency Communication and Information Office is able to provide good work productivity by aligning the role of personal narratives as an employee, husband or wife and as a parent.